The impact of social media influencers on political participation in Malaysia - Suhana Saad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores the impact of social media influencers on political participation in Malaysia, with a focus on their growing role in shaping digital political discourse. Based on qualitative analysis of secondary data from academic literature and credible online sources, the paper proposes a conceptual framework that explains how influencers promote political engagement through specific communication strategies and psychological processes. Influencer characteristics such as credibility, personal appeal, and the formation of parasocial relationships are found to foster emotional connections and enhance the effectiveness of political messaging. These factors contribute to increased civic participation both in digital spaces and real-world settings. The study also introduces the concept of micro-level interactions, referring to the everyday and informal exchanges between influencers and their followers, which serve as building blocks for broader shifts in political attitudes and behaviours. While the findings highlight the transformative potential of influencers in mobilising political awareness and action, they also raise concerns regarding misinformation, a lack of transparency, and the ethical implications of politically motivated content. The study offers a theoretical foundation for understanding how social media influencers affect political behaviour in Malaysia, and it provides insights that can inform future research and policy aimed at promoting accountability and safeguarding democratic values in the digital age.